1975
DOI: 10.1093/geronj/30.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Postural Sway in Women

Abstract: The effects of aging on postural sway in upright and forward lean stance were investigated. Postural sway was measured on a center of gravity apparatus using two age groups of female subjects 20 to 30 years old and 70 to 80 years old. The older adults demonstrated significantly larger sway areas than the young adults in both stance positions. The patterning of the center of gravity projections on the base of support tended to be similar under all conditions except in the young adults/upright position where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 0 publications
8
58
0
Order By: Relevance
“…This review has shown that balance evaluations are very different, both in protocols and in measurement methods, and that direct comparisons among studies and data interpretation are extremely limited. Many experimental protocols indicated that increased postural sway in older adults is well documented and research findings highlighted a correlation between postural sway and increased risk of falling not only on a static board (Baloh et al 1994;Benjuya et al 2004;Billot et al 2010;Fernie et al 1982;Hasselkus & Shambes 1975;Kang et al 2009;Lajoie et al 2002;Lord et al 1994;Maki et al 1994;Melzer et al 2004;Stel et al 2003), but also on an unstable board (Nardone et al 1994;Nardone et al 2000;Woollacott & Shumway-Cook 1990;Wolfson et al 1994;Rogers et al 2001). All Medial lateral sway in both the conditions (eyes open and closed) was found to be a distinguishing variable between older "fallers" and "non-fallers" in both static and dynamic narrow stance condition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review has shown that balance evaluations are very different, both in protocols and in measurement methods, and that direct comparisons among studies and data interpretation are extremely limited. Many experimental protocols indicated that increased postural sway in older adults is well documented and research findings highlighted a correlation between postural sway and increased risk of falling not only on a static board (Baloh et al 1994;Benjuya et al 2004;Billot et al 2010;Fernie et al 1982;Hasselkus & Shambes 1975;Kang et al 2009;Lajoie et al 2002;Lord et al 1994;Maki et al 1994;Melzer et al 2004;Stel et al 2003), but also on an unstable board (Nardone et al 1994;Nardone et al 2000;Woollacott & Shumway-Cook 1990;Wolfson et al 1994;Rogers et al 2001). All Medial lateral sway in both the conditions (eyes open and closed) was found to be a distinguishing variable between older "fallers" and "non-fallers" in both static and dynamic narrow stance condition .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently "a recalled fall was the most important predictor for future falls" (Gerdhem Increased postural sway in older adults is well documented (Hasselkus & Shambes 1975) and greater amounts of postural sway are correlated to increased risk of falling (Fernie et al 1982). Mean Sway Area in the medial-lateral, anterior-posterior directions, and Mean Sway Velocity were found to be higher in fallers (Fernie et al 1982;Maki et al 1994;Melzer et al 2004).…”
Section: Static Balance and Fallsmentioning
confidence: 99%
“…Historically, the human movement domain has been studied in both young and old adult locomotion [41][42][43] and standing posture [e.g., [44][45][46][47] separately with little emphasis on the reacquisition of postural stability following a step or sequence of steps. Nevertheless, it is well known that older adults experience more problems with postural control when they are required to move through or change their position with respect to the environment [40,48].…”
Section: Aging and The Time To Stability In Postural Controlmentioning
confidence: 99%
“…Human balance is maintained through a complex process involving sensory detection of body motion, integration of sensorimotor information within the central nervous system, and the execution of appropriate musculoskeletal responses 6) . Factors influencing balance such as age 7,8) , muscle weakness 9) , vibration sense 10) , respiration 11) , and visual input 12) have been studied. However there have been no studies on the effect of muscular fatigue on balance yet.…”
Section: Introductionmentioning
confidence: 99%